Representation of Form and Educational Values in Pattuqduq Kumba Dance: Local Cultural Values in the Educational Curriculum - Ahmad, Meyke Pracillia Utami; Syahrir, Nurlina; Padalia, Andi (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study's objective is to analyze the cultural values and uniqueness of the form and structure of this dance as a representation of the identity of the Mandar community in the field of education. This study uses a qualitative approach with a descriptive analytical research method. Data collection techniques include questionnaires, interviews, and documentation. We analyzed the data using qualitative analysis techniques. The results of the study indicate that the Pattuqduq Kumba Dance contains religious values, as seen from its role in traditional rituals that symbolize gratitude to God and respect for ancestors. The value of togetherness is reflected in the simultaneous movements of the dancers, which strengthen the spirit of mutual cooperation and social relations. In addition, the educational value in this dance functions as a medium for cultural education for the younger generation, teaching the preservation of tradition and understanding the symbolism of movement. The beauty of this dance lies in the harmony between movement, traditional music, and typical costumes that reflect the refinement of the art of the Mandar community. The structure of the dance, which is divided into three parts—opening, content, and closing—as well as the use of traditional properties such as fans and scarves, adds to the uniqueness and richness of its meaning. This study confirms that the Pattuqduq Kumba Dance is not only a performing art but also a symbol of life, local wisdom, and the close relationship between humans and nature, and it acts as a medium of education. This dance is an important medium for preserving culture and a means of strengthening the identity of the Mandar people amidst the challenges of modernization and is the basis for strengthening the curriculum, especially arts education.